Gerd Bornheim Reader of Hegel’s Aesthetics (Revista Eletrônica Estudos Hegelianos, 2024)
This article analyzes Gerd Bornheim’s reading of Hegel’s aesthetics in order to show in what sense it plays a fundamental role in the Brazilian philosopher’s thinking on the question of History. In addition, it is a question of looking at the panorama of philosophical debates in the city of Rio de Janeiro in the early 1990s to show how the fact that Bornheim was reading and discussing Hegel and Marx went against the dominant trend of the time, which was strongly marked by resistance to both thinkers due to the collapse of the Soviet system in 1989. Although in Dialética Bornheim aligned himself with Heidegger to critique the notion of totality in Hegel’s philosophy of history, he did not adhere to the Heideggerian proposal of a “return to origin”, popular in philosophy departments in Rio de Janeiro at the time. Arguing that the theme of sensibility was itself an obstacle to Hegel’s idealism, Bornheim sought to construct a meaning for history based on the assumption of the theme of difference in the 20th century philosophy.